المرونة الاستراتيجية كمدخل للإبداع التسويقي و تحقيق التميّز في أداء المؤسسات الإقتصادية الجزائرية- دراسة ميدانية – Strategic Flexibility As An Input To Marketing Innovation And Achieving Excellence In The Performance Of Algerian Economic Institutions– A Field Study – - بوفاس الشريف; بلايلية الربيع (My University, 2017)
في ظل التحولات المتسارعة التي يشهدها عالم الأعمال يرتبط تحقيق التميز بقدرة المؤسسات الاقتصادية على تلبية المتطلبات الحالية، و إشباع التوقعات المستقبلية لكافة المتعاملين، إذ لم يعد تميّز الأداء يقتصر فقط على تحقيق النمو و زيادة الفوائض المالية، بل تجاوز ذلك ليشمل أولويات أخرى ذات منفعة تستوجب ضرورة التكيف السريع بأقل التكاليف مع المعطيات الجديدة بما في ذلك متطلبات الحماية البيئية و الاجتماعية، وقد رافق ذلك توجه المؤسسات الاقتصادية خاصة الصناعية منها إلى مراجعة استراتيجياتها الحالية مع تبنيها مبدأ المرونة في تنفيذها. تمّ التوصل في الجانب الميداني إلى وجود علاقة تأثير ذات دلالة إحصائية بين الإبداع في عناصر المزيج التسويقي بدلالة مؤشراته مجتمعة مع التميز في أداء مطاحن بلغيث بسوق اهراس بدلالة مؤشراته مجتمعة، كما خلصت الدراسة إلى جملة من النتائج و تقديم بعض التوصيات. In light of the rapid changes taking place in the business world has been associated with the ability to achieve excellence of economic institutions to meet current requirements and satisfy future expectations of all stakeholders,it is no longer characterize the performance limited only to achieve growth and increase the financial surpluses, but go beyond that to include other public utility requiring the need to quickly adapt to the lowest possible costs with the new data, including environmental protection requirements and social priorities, this was accompanied by a private guide industrial economic institutions, including a review of current strategies adopted with the principle of flexibility in its implementation in order to achieve a positive compatibility with the surrounding environment and lasting excellence in performance through the adoption of flexible mechanisms to activate the requirements of sustainable development at the level of their production and marketing. In its practical part, this study also has concluded a series of results and provided a set of recommendations.